VALIDATION OF TUNING FORK TEST IN STRESS FRACTURES AND ITS COMPARISON WITH RADIONUCLIDE BONE SCAN - Fatima, Syeda Tatheer; Jeilani, Asif; Duha, Mazhar -ud-; Abbasi, Nadeem Zia; Khan, Amjad Aziz; Khan, Kamran; Sheikh, Abdul Samad; Ali, Furqan; Memon, Khalid Hussain (Journal of Ayub Medical College Abbottabad, 2012)
Background: Stress fractures are quite common both in athletes and military recruits. The purpose of the study was to evaluate the efficacy of tuning fork in stress fractures by comparing it with three phase bone scan. Methods: The current study examined 55 subjects whose age ranged 18-28 years. X-rays of all the subjects were unremarkable. After history and clinical examination tuning fork test (TFT) was performed on each case by placing 128 Hertz vibrating tuning fork on the site of pain (underlying bony surface) of tibia or fibula. Each case was scanned using triple phase bone scintigraphy. Results: Fiftyfive patients had a total of 67 stress fractures, out of which 53 were picked up by TFT. Sensitivity of TFT was found to be 79% and specificity of 63%. Positive and negative predictive values were 88% and 46% respectively. Conclusion: Tuning fork test is a simple and easy approach of diagnosing stress fractures which can be performed even by athletics and military trainers. Management should be initiated in patients who have history of stress related below-knee pain and positive tuning fork test without waiting for bone scintigraphy. For complicated cases the bone scan is the gold standard for diagnosis. Keywords: stress fracture, bone scan, tuning fork test